PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS INQUIRY UNTUK SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA - Ahde Fitri (Pendidikan Matematika | STKIP YM Bangko, 2021)
The use of math learning tools can help smooth the process of defense. However, existing tools have not been able to engage students actively in making discoveries in order to build a conceptual understanding of the material learned. Lack of involvement of students in developing students; understanding of the concept of cause is easy to forget the material. This results in lower student learning outcomes. Therefore we need a device that can help student learning, the inquiry. Learning device is expected to lead the students to be actively involved in doing findings against the concept of the material to be studied so that the concept last long in the memory of the students. The purpose of this study is to develop inquiry is valid, practical and effective. This type of research is the development of research. This study uses a model of 4-D which consists of 4 stages: stage define, design, develop and disseminate. Inquiry validated by mathematics and language experts. Practicality is measured through observation implementation of learning and questionnaire responses of students and teachers. The effectiveness was measured through observation activities and student learning outcomes. The data were analyzed descriptively with the results of the validation are valid in terms of content and construct. At this stage of the practicalities, the result that the inquiry is practical to use. The use of inquiry can increase the activity and student learning outcomes. Mastery level student learning outcomes reached 76%. This means the device is effective in improving student learning outcomes. The result showed that the inquiry has developed a valid, practical and effective to use as a learning tool for mathematics for junior high school students VIIII.